CLINICAL EVALUATION OF POTENTIAL ANTI-INFLAMMATORY EFFECT OF VITAMIN D3 ADJUVANT THERAPY FOR CHRONIC ASTHMA IN IRAQI PATIENTS - Abbas, Rasha Saadi; Abdulridha, Manal Khalid; Shafek, Mostafa Abdalfatah (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: This study was designed to evaluate the potential anti-inflammatory effect of vitamin D3 supplementation in Iraqi patients with chronic asthma. Methods: Forty-four candidate patients were diagnosed with asthma during their visit to hospital allocated as 20 patients assigned to receive conventional therapy for asthma and 24 patients assigned to receive conventional therapy for asthma plus 2000 I. U vitamin D3 tablet for three months period. Also, 30 apparently healthy subjects were included in the study as a control group. Pulmonary function test, serum 25-OH vitamin D levels, serum Interlukin-10 (IL-10) levels, serum tumor necrosis factor alpha (TNF-Î±) levels were measured before and after three months therapy. Results: After three months treatment, there was a highly significant improvement in both measured and percentage of predicted value of pulmonary function test (PFT) compared to the pre-treatment value for both group 1 and group 2 patients (p<0.01). Also, a highly significant increase in total endogenous vitamin D level in group 2 when compared to group 1 patients after three months period (p<0.01). Group 2 patients presented with a significant increase in mean IL-10 after three months of treatment when compared to pre-treatment level (p<0.05). The mean TNF-Î± level was increased non-significantly in both study groups, but the higher level was found in group 1 patients than in group 2 patients when compared to pre-treatment level (p>0.05). Conclusion: There was a significant increase in the level of anti-inflammatory biomarker interleukin-10 (IL-10), though no clear effect on tumor necrosis factor-Î± (TNF-Î±) was noticed after three months treatment with vitamin D3 supplementation.